Management of a rare case of idiopathic multiple unerupted impacted permanent teeth in an adult female patient - Karunakar Shetty; Mahesh Kumar; Susan Amanna; Srirangarajan Sridharan; Satyanarayan Reddy (Wolters Kluwer Medknow Publications, 2016)
This clinical case report describes the multi-disciplinary approach in the management of an unusual presentation of idiopathic multiple unerupted impacted permanent teeth in a 20-year-old female patient. The case was unique in that, not only were there multiple missing permanent teeth, but also over retained deciduous teeth and attrited existing permanent teeth with loss of vertical dimension of occlusion. Since the patient was young, it was decided to retain all the erupted permanent teeth and extract the infected deciduous teeth with the objective of fabricating overlay complete dentures. This is a simple, reversible and an economical treatment modality, which satisfies both the esthetic and functional demands where the extraction of teeth is not generally indicated and, in addition, provides a stable occlusion.